2017
DOI: 10.1002/ecy.1630
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐mycorrhizal interactions mediate plant community coexistence by altering resource demand

Abstract: As the diversity of plants increases in an ecosystem, so does resource competition for soil nutrients, a process that mycorrhizal fungi can mediate. The influence of mycorrhizal fungi on plant biodiversity likely depends on the strength of the symbiosis between the plant and fungi, the differential plant growth responses to mycorrhizal inoculation, and the transfer rate of nutrients from the fungus to plant. However, our current understanding of how nutrient-plant-mycorrhizal interactions influence plant coexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 52 publications
2
46
0
Order By: Relevance
“…If and where the microbe‐mediated soil nutrient partitioning does occur in forest, it may not only increase resource extraction by mixed‐species plant communities but also facilitate plant species coexistence in complex resource environments. Although plant–mycorrhiza interactions have been repeatedly shown to affect the coexistence of different plant species and biodiversity‐productivity relationships (Bennett et al., ; Jiang, Moore, Priyadarshi, & Classen, ; Klironomos, McCune, Hart, & Neville, ; Luo, De Deyn, Jiang, & Yu, ; Maherali & Klironomos, ; Teste et al., ; van der Heijden, Bardgett, & van Straalen, ; van der Heijden et al., ; Wagg et al., ), our case study reveals the role of soil microbes in plant N partitioning. Our species pool contained only three tree species, and therefore, we cannot extrapolate the results to a broader set of mature canopy trees in natural forest.…”
Section: Discussionmentioning
confidence: 99%
“…If and where the microbe‐mediated soil nutrient partitioning does occur in forest, it may not only increase resource extraction by mixed‐species plant communities but also facilitate plant species coexistence in complex resource environments. Although plant–mycorrhiza interactions have been repeatedly shown to affect the coexistence of different plant species and biodiversity‐productivity relationships (Bennett et al., ; Jiang, Moore, Priyadarshi, & Classen, ; Klironomos, McCune, Hart, & Neville, ; Luo, De Deyn, Jiang, & Yu, ; Maherali & Klironomos, ; Teste et al., ; van der Heijden, Bardgett, & van Straalen, ; van der Heijden et al., ; Wagg et al., ), our case study reveals the role of soil microbes in plant N partitioning. Our species pool contained only three tree species, and therefore, we cannot extrapolate the results to a broader set of mature canopy trees in natural forest.…”
Section: Discussionmentioning
confidence: 99%
“…By definition, shallow soils have a low soil volume, and soil depth tend to be limited by the shallow bedrock in karst regions. This shallow bedrock may enhance horizontal but not vertical root growth (Estrada‐Medina, Graham, Allen, Jiménez‐Osornio, & Robles‐Casolco, ; Nie, Chen, Wang, & Ding, ), and may thereby promote the accumulation of soil organic matter, as well as soil C and N, by bringing together rainwater, nutrients, and root exudates in horizontally distributed spots (Göransson, Edwards, Perreijn, Smittenberg, & Venterink, ; Jiang, Moore, Priyadarshi, & Classen, ; Zhang et al, ). Hu et al () also found that soil depth and bulk density were important factors affecting the accumulation of SOC after natural restoration in our study area.…”
Section: Discussionmentioning
confidence: 99%
“…, Jiang et al. ). As shrubs expand in the arctic due to climatic warming, they will expand their influence on the soils they grow in and lead to feedbacks that will shape how these ecosystems respond to and develop under a warmer and more variable world (e.g., Buckeridge et al.…”
Section: Discussionmentioning
confidence: 99%